Preparation and evaluation of neem seed oil nanocream using sucrose monoester (laurate) / Zakiah Bakar Ali - Bakar Ali, Zakiah (2012)
The formation of oil in water (o/w) nanocream containing neem oil which has droplet size < 200 nm was formulated and developed for application of topical product. Neem oil, which originated from India, was used in this study due to its wide range of insecticidal and various types of biomedical properties. An experimental study of neem oil nanoemulsion was conducted through various formulations consisting of various ratios of neem oil, sucrose laurate (1695) and glycerol. The particle sizes and visual observation of the prepared neem oil nanophase gel were analyzed and the best formulation was selected for the preparation of neem oil nanocreams with the addition of different concentrations of thickening agent such as Carbopol 934 and 940 into the system. Results obtained showed that formulations of 10%, 15% and 20% neem oil; 1.0% Carbopol 940 were found to have the most favorable characteristic with small droplet size (<200 nm), low polydispersity index (< 0.2 PDI), good cream rheology properties plus great stability.